Literature Review the Effect of Headmaster Leadership on Teacher Performance, Loyalty and Motivation - M. Rizky Mahaputra; Farhan Saputra (DINASTI RESEARCH, 2021)
The Literature Review article on the Effect of Headmaster Leadership on Teacher Performance, Loyalty and Motivation is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature article are: 1) Teacher performance is influenced by the Headmaster Leadership; 2) Loyalty is influenced by the Headmaster Leadership; and 3) Motivation is influenced by the Headmaster Leadership. In addition to these factors, there are other factors that are influenced by the Headmaster Leadership, namely: Salary, Workload, Work Culture and Work Environment.